The Mt John University Observatory search for Earth-mass planets in the habitable zone of α Centauri. Issue 2 (April 2015) - Endl, Michael; Bergmann, Christoph; Hearnshaw, John; Barnes, Stuart I.; Wittenmyer, Robert A.; Ramm, David; Kilmartin, Pam; Gunn, Fraser; Brogt, Erik
Abstract The 'holy grail' in planet hunting is the detection of an Earth-analogue: a planet with similar mass as the Earth and an orbit inside the habitable zone. If we can find such an Earth-analogue around one of the stars in the immediate solar neighbourhood, we could potentially even study it in such great detail to address the question of its potential habitability. Several groups have focused their planet detection efforts on the nearest stars. Our team is currently performing an intensive observing campaign on the α Centauri system using the High Efficiency and Resolution Canterbury University Large Échelle Spectrograph (Hercules) at the 1 m McLellan telescope at Mt John University Observatory in New Zealand. The goal of our project is to obtain such a large number of radial velocity (RV) measurements with sufficiently high temporal sampling to become sensitive to signals of Earth-mass planets in the habitable zones of the two stars in this binary system. Over the past few years, we have collected more than 45 000 spectra for both stars combined. These data are currently processed by an advanced version of our RV reduction pipeline, which eliminates the effect of spectral cross-contamination. Here we present simulations of the expected detection sensitivity to low-mass planets in the habitable zone by the Hercules programme for various noise levels. We also discuss our expected sensitivity to the purported Earth-mass planet in a 3.24-day orbit announced by Dumusque et al. (2012).